2021
DOI: 10.3390/brainsci11060762
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypies in the Autism Spectrum Disorder: Can We Rely on an Ethological Model?

Abstract: Background: Stereotypic behaviour can be defined as a clear behavioural pattern where a specific function or target cannot be identified, although it delays on time. Nonetheless, repetitive and stereotypical behaviours play a key role in both animal and human behaviour. Similar behaviours are observed across species, in typical human developmental phases, and in some neuropsychiatric conditions, such as Autism Spectrum Disorder (ASD) and Intellectual Disability. This evidence led to the spread of animal models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 154 publications
0
11
0
Order By: Relevance
“…Previous studies have found that several neurotransmitters of ASD, such as serotonin and dopamine, are associated with repetitive and stereotypical behaviors (Kondaurova et al, 2023; Pavăl, 2017). In animal experiments, striatal dopamine can inhibit the occurrence of stereotyped and repetitive behaviors by affecting the pathway balance of basal ganglia (Gandhi & Lee, 2021; Keller et al, 2021). With the emergence and continuous development of fMRI technology, scholars have found that the generation of stereotyped and repetitive behaviors is closely related to executive dysfunction (Fatima, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that several neurotransmitters of ASD, such as serotonin and dopamine, are associated with repetitive and stereotypical behaviors (Kondaurova et al, 2023; Pavăl, 2017). In animal experiments, striatal dopamine can inhibit the occurrence of stereotyped and repetitive behaviors by affecting the pathway balance of basal ganglia (Gandhi & Lee, 2021; Keller et al, 2021). With the emergence and continuous development of fMRI technology, scholars have found that the generation of stereotyped and repetitive behaviors is closely related to executive dysfunction (Fatima, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Aetiologically, the two syndromes are considered as resulting from the overlapping of genetic and environmental factors that have important effects on brain development; this is proven to cause subsequent impairments in cognitive functioning. Autism is thought to be underpinned by abnormalities in brain circuitry related to social cognition and communication, while in IDD cognitive impairments are related to logical-deductive skills (Totsika et al 2010;Bertelli et al 2015aBertelli et al , 2015bKeller et al 2021).…”
Section: Considerations On the Analyses On Psychopathological And Cog...mentioning
confidence: 99%
“…Therefore, potential common underlying brain network abnormalities are more difficult to detect ( Langen et al, 2011 ). Nonetheless, associations with underlying structural and functional brain abnormalities have been described ( Lewis and Kim, 2009 ; Muehlmann and Lewis, 2012 ; Gao and Singer, 2013 ; Francis et al, 2014 ; Péter et al, 2017 ; Martino and Hedderly, 2019 ; Keller et al, 2021 ; Ganos et al, 2022 ), most consistently an involvement of basal ganglia structures and sensitivity to changes in dopaminergic tone. For example, motor stereotypies can be induced pharmacologically in animal models by dopamine receptor agonists or drugs that increase synaptic dopamine ( Péter et al, 2017 ), and vascular lesions in different basal ganglia structures can provoke repetitive phenomena ( Benke et al, 2000 ; Langen et al, 2011 ; Péter et al, 2017 ; Ganos et al, 2022 ).…”
Section: Repetitive Behaviors and Basal Ganglia Functionmentioning
confidence: 99%